O território camponês como dimensão educativa: desafios e possibilidades da Educação do Campo em Grajaú-MA - Marcos Nicolau Santos da Silva (2018)
The objective of this research was to analyze the material and intangible conditions of the schools of Grajaú-MA field and problematize the conception of education of the field offered in the municipality. Moreover, it was also aimed at evaluating the teaching-learning of geography in the research schools. The methodology of the research was in the qualitative research, accompanied by research in official databases (school census, IDEB, IBGE, INCRA), the Municipal secretariat of Education of Grajaú (SEMED) and in the field research with the schools. The selected field schools were the Agricultural Family School of Boa Vista Project (EFA de Grajaú), high school technical in farming, Municipal School Bom Futuro, Municipal School Pastor José Pires and Municipal School Professor José Rufino Sobrinho. The last three schools are elementary school, whereas, except the Municipal School Bom Futuro, all are located in rural settlements. We use participant research as a methodological foundation to guide field activities. In each school, the activities were developed in three moments with the students: the first meeting was held the presentation of the proposal of research and playful activities to improve the contact with the students, besides diagnosing the problems of the school and communities; the second meeting developed a map spoken of the problems indicated in the first meeting, used as a methodological tool for Participatory Rural Diagnosis, as well as the proposition of solutions to listed problems; in the third meeting, interviews were conducted with the school managers and the teachers. The results showed that, in practice, the education of the field does not exist in Grajaú, because the schools reproduce the same model of education of the city. The results showed that in practice the education of the field does not exist in Grajaú, because the schools reproduce the same model of education in the city. All schools presented precarious conditions of infrastructure, reproducing the same model of education in the Brazilian field, namely: inadequate physical structure, classrooms without thermal comfort, lack of classroom for all classes, class multisseriadas full and difficult working conditions for the teacher, insufficient snack, little diversified or with low nutritional content, school transport insecure, precarious, as well as roads with low traffic condition, lack of teachers Periodically, among others. This precariousness is reflected in the form of deterritorialization, leading students from the field to social exclusion. The precarious education is therefore an obstacle to the development of the education of the countryside and, by extension, weakes the peasant territories. In addition to this, the political dispute in which the education of the municipality, specifically in the field, is subordinated to the political power, indicating the positions, the professors and other servants that manage and operate in schools, which corroborates the weakening of the Education of Campo in Grajaú.